PENERAPAN PENDIDIKAN KARAKTER DENGAN PROGRAM SEKOLAH RAMAH ANAK (SRA) DALAM PERSPEKTIF PENDIDIKAN AGAMA ISLAM DI MTSN - Rosyalia; Jumari (EL-Islam, 2022)
Abstract: The purpose of education is to make students active in expanding their potential. With continuous training towards abetter direction and making habits embedded in a person is the goal of character education. Article28B:2 of the 1945 Constitution states that every child has the right to survive, grow, develop, and is entitled to protection from acts of violence and discrimination. The focus of this research includes: how is character education in the perspective of Islamic religious education in the scope of MTsN, how child-friendly schools are in the scopeo fMTsN, and how is the implementation of character education with child-friendly school programs in the perspective of Islamic religious education in the scope of MTsN. These methods include: qualitative research approach, the type of case study research. This study uses primary data sources because they come from school principals, educators, parents, and students. Data collection techniques are observation, interviews, anddocumentation.This study uses triangulation of sources to obtain data from all aspects related to the application of character education. Conclusions include: Character education teaches children to form personalities including three elements: cognitive, affective, and psychomotor, Child Friendly Schools prioritize guiding and prioritizing children's rights needs by emphasizing anti violence, no bullying, implementation with routine habituation, spontaneous habituation such as applying 3S while educators applied to the RPP according to the subject.